2018
DOI: 10.1016/j.exer.2018.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of GLUT1 in mouse lens epithelium leads to cataract formation

Abstract: The primary energy substrate of the lens is glucose and uptake of glucose from the aqueous humor is dependent on glucose transporters. GLUT1, the facilitated glucose transporter encoded by Slc2a1 is expressed in the epithelium of bovine, human and rat lenses. In the current study, we examined the expression of GLUT1 in the mouse lens and determined its role in maintaining lens transparency by studying effects of postnatal deletion of Slc2a1. In situ hybridization and immunofluorescence labeling were used to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…For example, Fidler et al ( 10) observed a similar metabolic flexibility when they deleted GLUT1 from platelets, which subsequently increased their use of amino acids. In addition, we observed a similar compensation by amino acids when we deleted GLUT1 from mouse lens epithelium and found a decrease in amino acids in the aqueous humor of transgenic mice, indicating an increase in amino acid oxidation by the mouse lens under glucose deprivation (46). Alternatively, glucose derived from the inner retinal vasculature, perhaps along with amino acid oxidation, could be sufficient to maintain the observed degree of photoreceptor viability.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…For example, Fidler et al ( 10) observed a similar metabolic flexibility when they deleted GLUT1 from platelets, which subsequently increased their use of amino acids. In addition, we observed a similar compensation by amino acids when we deleted GLUT1 from mouse lens epithelium and found a decrease in amino acids in the aqueous humor of transgenic mice, indicating an increase in amino acid oxidation by the mouse lens under glucose deprivation (46). Alternatively, glucose derived from the inner retinal vasculature, perhaps along with amino acid oxidation, could be sufficient to maintain the observed degree of photoreceptor viability.…”
Section: Discussionmentioning
confidence: 53%
“…Sections were incubated at room temperature with secondary antibodies (Table 1) and with DAPI, and then imaged on an LSM 780 NLO laser scanning microscope (Carl Zeiss, Oberkochen, Germany) using ApoPlan ϫ63/1.4 objective and EC NeoPlan ϫ10/0.3 objective. For hematoxylin and eosin (H&E)-stained sections, methanol:acetic acid fixed eyes were embedded in paraffin and 10-m sections were cut as described previously (46). Paraffin sections were deparaffinized using xylene and rehydrated in a graded series of ethanol then water and used for immunofluorescence labeling as described above.…”
Section: Methodsmentioning
confidence: 99%
“…Another study showed glucose concentrations in anterior aqueous humor of 137 mg/100 ml (7.6 mM), and it was speculated that glucose concentration was ∼100 mg/100 ml (5.5 mM) in extracellular lens fluid ( Kuck, 1965 ). Glucose in the lens cell is primarily from aqueous humor ( Swarup et al, 2018 ), and glucose is converted into glucose-6-phosphate rapidly inside cells ( Kinoshita, 1965 ). Although the gradient of glucose from the cortex to the nucleus has not been directly measured, we would expect that glucose in the microfluidic solution is higher than that inside the lens cells, and like GSH, there is a gradient, with the highest level of glucose found in cortical fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse experiments were performed in accordance with the National Institutes of Health guidelines and the protocol approved by the Institutional Animal Care and Use Committee of West Virginia University. MPC1 RNA in situ hybridization, metabolite analysis by mass spectrometry, EM, immunohistochemistry, and other methods were performed as reported (38,39) and described in details in SI Appendix.…”
Section: Methodsmentioning
confidence: 99%